Kant and the Origins of Totalitarianism - Siebers, Tobin (Philosophy and literature, 1991)
Tobin Siebers KANT AND THE ORIGINS OF TOTALITARIANISM The moral principle that it is one's duty to speak the truth if it were taken singly and unconditionally, would make all society impossible. We have the proof of this in the very direct consequences which have been drawn from this principle by a German philosopher, who goes so far as to affirm that to tell a falsehood to a murderer who asked us whether our friend, of whom he was in pursuit, had not taken refuge in our house, would be a crime. —Benjamin Constant (1797) In a certain sense, insofar as it wishes to deny, to correct, or to surpass him, modern moral philosophy remains something ofa postscript to Kant. But we have not yet learned to see that modern responses to Kant may well be derived from and surpassed by the modernity of Kant's own ethics. This, at least, will be my argument here. Indeed, it sometimes seems that the express purpose of modern ethics is to occult Kant's modernity, either by viewing him as a representative of the outmoded and failed philosophy of the Age of Reason or as the slave of duty, the one concept that has come to be treated with the greatest suspicion by ethical thought in the twentieth century. Hitler, it seems, exposes how thoroughly unmodern are Kant's claims for reason and duty. The dream ofreason supposedly produces Hitler's Germany, and after Auschwitz, the concept of duty acquires the clear and shameful distinction ofbeing able tojustify any action, no matter how monstrous. Modern ethical thinkers associate Kantian reasoning and duty with a kind ofmonstrosity as well. My duty is to obey the imperative ofreason, Kant says, and not to look to the world of experience. As long as I do my duty, I will not be held responsible for the consequences of my actions. Few attitudes are as repulsive to modern thought. Philosophy and Literature, © 1991, 15: 19-39 20Philosophy and Literature Alasdair Maclntyre's A Short History of Ethics captures the modern critical attitude toward Kant and alludes to the historical origins of our distaste for him: Anyone educated into the Kantian notion of duty will, so far, have been educated into easy conformism with authority. . . . [Kant] hated servility and valued independence of mind. Paternalism, so he held, was the grossest form of despotism. But the consequences of his doctrines, in German history atleast, suggest that the attempt to find a moral standpoint completely independent ofthe social order may be a quest for an illusion, a quest that renders one a mere conformist servant of the social order much more than does the morality ofthose who recognize the impossibility of a code which does not to some extent at least express the wants and needs of men in particular social circumstances.1 "Consequences" represents as well as any word what modern moral philosophers have singled out as being of primary importance in ethics. Both Benjamin Constant and Alasdair Maclntyre agree on this point. The modern world, they explain, brings unexpected consequences from every action, and we moderns no longer believe that simple rules, codes, or imperatives are capable of regulating the disorder and unpredictability of moral life. Strong adherence to such codes makes society impossible. Rather, we have to look to the consequences, and the only method of doing this is to immerse ourselves in the dense texture and fabric of our society, to come to know ourselves as social beings, that we might understand the network of relations in which our actions take place. However we describe Kant's ethics, whether as individualistic or as subservient to the authority of duty, it seems to fail to meet this description of how things are. First, Kant's almost solipsistic emphasis on the reasoning individual, in which the good will obeys no one but tumor herself, appears to miss the point: in the modern world of consequences , we must attend to political life and its intricate web of relationships . There is no place for a morality independent of the social order. Kant's preference for moral autonomy appears inadequate as a response to the modern situation in particular and...